Peran Guru BK dalam Mengidentifikasi Kesulitan Belajar Matematika pada Siswa Kelas VIII di SMPN 2 Salatiga - Syarif Meisya Putri Wahyuni; Dian Larasati; Chotibul Umam; Muhammad Rizal Safri; Andar Ifazatul Nurlatifah (Institut Agama Islam Negeri Padangsidimpuan, 2026)
Learning difficulties in mathematics are commonly experienced by junior high school students and have an impact on low academic achievement and learning motivation. This study aims to describe the role of guidance and counseling teachers in identifying mathematics learning difficulties among eighth-grade students at SMPN 2 Salatiga and to identify the factors influencing these difficulties. This research employed a descriptive qualitative approach with data collection techniques including in-depth interviews and observations. The research subjects consisted of guidance and counseling teachers and mathematics teachers. The findings indicate that guidance and counseling teachers identify students’ mathematics learning difficulties through analysis of academic achievement, coordination with mathematics teachers, and limited observation of students’ learning behaviors. Mathematics learning difficulties are characterized by low conceptual understanding, the need for repeated explanations, and difficulties in solving varied problem forms. The contributing factors include internal factors such as low learning motivation, lack of self-confidence, and learning anxiety, as well as external factors including the level of material difficulty, teaching methods, use of technology, and limited parental support. The study also reveals collaboration between guidance and counseling teachers and mathematics teachers in identifying learning difficulties, although counseling services have not yet been optimally implemented. These findings highlight the importance of strengthening the role of guidance and counseling services to support students in overcoming mathematics learning difficulties.Kesulitan belajar matematika merupakan permasalahan yang sering dialami siswa Sekolah Menengah Pertama (SMP) dan berdampak pada rendahnya hasil belajar serta motivasi siswa. Penelitian ini bertujuan untuk mendeskripsikan peran guru Bimbingan dan Konseling (BK) dalam mengidentifikasi kesulitan belajar matematika pada siswa kelas VIII di SMPN 2 Salatiga serta faktor-faktor yang memengaruhinya. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data berupa wawancara mendalam dan observasi. Subjek penelitian meliputi guru BK dan guru matematika. Hasil penelitian menunjukkan bahwa guru BK mengidentifikasi kesulitan belajar matematika siswa melalui analisis hasil belajar, koordinasi dengan guru matematika, serta observasi terbatas terhadap perilaku belajar siswa. Kesulitan belajar matematika ditandai dengan rendahnya pemahaman konsep, kebutuhan akan penjelasan berulang, serta kesulitan dalam menyelesaikan variasi soal. Faktor penyebab kesulitan belajar meliputi faktor internal berupa rendahnya motivasi belajar, kurangnya rasa percaya diri, dan kecemasan belajar, serta faktor eksternal berupa tingkat kesulitan materi, metode pembelajaran, penggunaan teknologi, dan kurangnya dukungan orang tua. Hasil penelitian ini menegaskan pentingnya peran guru BK dalam mengidentifikasi kesulitan belajar matematika sebagai dasar pengembangan layanan bimbingan dan konseling yang lebih efektif..